1992
DOI: 10.1111/j.1600-0536.1992.tb05216.x
|View full text |Cite
|
Sign up to set email alerts
|

Further investigation of the prohapten concept: reactions to benzene derivatives in man

Abstract: p-Phenylenediamine (PPDA) is a strong contact sensitizer which is included in the standard patch test tray and which can also act as an indicator of allergy to related substances by virtue of cross-reactions. In a previous study, the pattern of cross-reactions between PPDA and related substances was investigated in the guinea pig to evaluate the prohapten concept. The results provided some support for this concept, but also indicated that a number of reactive intermediates might be behaving as haptens. This wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 12 publications
5
26
1
Order By: Relevance
“…Table 1. Association between selected genetic polymorphism and WBC counts in benzene-exposed workers and controls humans exposed to benzene oxidation products has also been described our findings are biologically plausible (Basketter and Liden, 1992).…”
Section: Discussionsupporting
confidence: 78%
“…Table 1. Association between selected genetic polymorphism and WBC counts in benzene-exposed workers and controls humans exposed to benzene oxidation products has also been described our findings are biologically plausible (Basketter and Liden, 1992).…”
Section: Discussionsupporting
confidence: 78%
“…The ability of PPD to elicit comparatively robust increases in IL-1␤ mRNA in cells derived from responder donors is intriguing because this chemical is usually regarded as being a prohapten, requiring metabolic conversion to, for example, Bandrowski's Base (BB) for allergenic activity. 24 It is of interest that in an investigation of the ability of LCs to provoke primary T lymphocyte proliferative responses to chemical allergens in vitro, Krasteva et al 25 found that although the parent molecule (PPD) induced responses in only one of six experiments, BB routinely caused primary sensitization. On the basis of the data that we report here, it could be argued that PPD does have some intrinsic allergenic potential or, alternatively, that the culture system employed possesses some metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Other inducers of ACD, such as phenols and phenylenediamine derivatives [4], have to be activated by oxidation to yield reactive electrophilic intermediates before addition to proteins can occur [4,5]. No complete antigen has been chemically defined and the chemical reaction between the hapten and the carrier protein in vivo is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Activated intermediates of two inducers of ACD, 1,4-benzoquinone 2 and 4-t-butyl-1,2-benzoquinone 3 ( fig. 2) were chosen as model haptens [4,8] and the outcome of the reaction of these haptens with the model peptide under physiologic conditions was analyzed. The adducts were isolated and their structures determined by nuclear magnetic resonance (NMR) and mass spectrometry (MS).…”
Section: Introductionmentioning
confidence: 99%